The Founder of Modern Geology Died 100 Years Ago:: The Scientific Work and Legacy of Eduard Suess - Şengör, A. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2015)
Eduard Suess (1831-1914) is probably the greatest geologist who ever lived. He died 100 years ago and left us the modern geology as we know it. His work ranged from paleontology through stratigraphy, geomorphology, urban geology, finally to tectonics. His magnum opus was the multi-volume Das Antlitz der Erde (The Face of the Earth), the greatest book in the history of geology. It is a complete description of the geology of the planet from the viewpoint of the theory of thermal contraction in Constant Prévost’s version, as modified by Suess. For all the admiration it caused it has been largely left unread and as a consequence geology lost some half a century until the invention of plate tectonics in 1965. This was in part, because the way Suess wrote the book made reading very difficult. The following is not a biography of Suess, but a review and evaluation of his work during the centenary of his death.